The Effect Design, Material and Information of Packaging on Consumer Behavior E-Commerce - Rosmiati, Rosmiati; Jamaluddin, Jamaluddin; Lidiana, Lidiana (JURNAL ADMINISTRASI KANTOR, 2023)
This study aims to determine the effect of packaging on e-comerce consumer behavior. Data from 84 articles were collected from indexed databases, with bibliometric analysis, Bibliometric analysis was conducted for data evaluation because it allows analysis of bibliographic material offering objective and reliable analysis. Systematic abstract search using Publish or Perish to identify articles that discuss the role of packaging on e-commerce consumer behavior in 2019 - 2023, identify behavioral issues and allow to know the new behavior of e-commerce consumers related to the latest packaging innovations. The results showed that there are 3 important factors that determine the behavior of e-commerce consumers, namely, packaging design, packaging material and information on packaging. The information provides transparency and builds trust between producers and consumers. useful for understanding changes in e-commerce consumer behavior.     Keywords : behavior of e-commerce consumers, packaging design, packaging material and information on packaging.